Evaluate the expression [tex]$6x - 2y + 5$[/tex] when [tex]$x = -2$[/tex] and [tex][tex]$y = -7$[/tex][/tex].

(Show your work)



Answer :

Certainly! Let's evaluate the expression [tex]\(6x - 2y + 5\)[/tex] given the values [tex]\(x = -2\)[/tex] and [tex]\(y = -7\)[/tex].

Here's a step-by-step solution:

1. Substitute the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] into the expression:

The expression is [tex]\(6x - 2y + 5\)[/tex]. We substitute [tex]\(x = -2\)[/tex] and [tex]\(y = -7\)[/tex]:
[tex]\[ 6(-2) - 2(-7) + 5 \][/tex]

2. Multiply the constants by the substituted values:

- First, calculate [tex]\(6 \times (-2)\)[/tex]:
[tex]\[ 6 \times (-2) = -12 \][/tex]
- Next, calculate [tex]\(-2 \times (-7)\)[/tex]:
[tex]\[ -2 \times (-7) = 14 \][/tex]

3. Substitute these results back into the expression:

Replacing the results we obtained, our expression now looks like this:
[tex]\[ -12 + 14 + 5 \][/tex]

4. Perform the addition and subtraction operations from left to right:

- First, add [tex]\(-12\)[/tex] and [tex]\(14\)[/tex]:
[tex]\[ -12 + 14 = 2 \][/tex]
- Next, add the result to [tex]\(5\)[/tex]:
[tex]\[ 2 + 5 = 7 \][/tex]

Therefore, the value of the expression [tex]\(6x - 2y + 5\)[/tex] when [tex]\(x = -2\)[/tex] and [tex]\(y = -7\)[/tex] is:
[tex]\[ \boxed{7} \][/tex]